Error and Mistake Analysis of Linguistic Components in the Writing Composition (RETAIN, 2016)
Error and Mistake Analysis of Linguistic Components in the Writing Composition Fani Puspita Utami English Education Program, Language and Art Faculty, State University of Surabaya utami.fani@yahoo.com Prof. Dr. Susanto, M.Pd. English Education Program, Language and Art Faculty, State University of Surabaya susantoniki@gmail.com Abstrak Penelitian ini memuat tentang jenis kesalahan pada tiga komponen kebahasaan; morfologi, sintaks, dan leksikal dalam komposisi tulisan siswa. Penelitian ini bertujuan untuk mengungkap bahwa kesalahan siswa tidak hanya tergolong ke error namun juga mistake. Terdapat tiga subjek yang mewakili tiga kelompok; tulisan siswa yang baik, rata-rata, dan buruk. Dari analisis yang dilakukan, kesalahan pada tulisan siswa tidak hanya tergolong dalam error saja sebagaimana penelitian terdahulu. Namun juga, terdapat kesalahan yang tergolong ke dalam mistake. Error pada morfologi ditemukan pada ketiga subjek sedangkan mistake pada morfologi hanya terdapat pada tulisan yang buruk. Error dan mistake pada sintaks ditemukan pada ketiga subjek. Lalu, error pada leksikal juga terdapat pada ketida subjek sedangkan mistake pada leksikal hanya terdapat pada tulisan yang rata-rata. Penelitian ini membuktikan bahwa kesalahan yang muncul selama proses pembelajaran tidak hanya tergolong ke dalam error namun juga mistake. Walaupun subjek penelitian ini adalah teks naratif, peneliti yakin bahwa siswa akan membuat kesalahan serupa dalam teks yang lainnya seperti teks dekskripsi, laporan, prosedur, dll. Keywords: Kesalahan, Analisis Kesalahan, Komponen Kebahasaan, Morfologi, Sintaks, Leksikal. Abstract This study comprises the two kinds of deviation in the three linguistic components; morphology, syntax, and lexical in the writing composition. It aims to find out that the learners’ deviations do not only belong to errors but also mistakes. There are three subjects in this study; a good writing composition, an average writing composition, and a poor writing composition. From the conducted analysis, the found deviations do not only belong to errors but also mistakes. The morphological errors are found in the three subjects while the morphological mistakes are only found in the poor writing composition. Then, both syntactical errors and mistakes are found in all subjects. Finally, the lexical errors are found in the good, average, and poor writing compositions yet the lexical mistakes are only found in the average writing composition. From the study, it was proven that the learners’ deviations do not only belong to errors but also mistakes. Although the compositions are narrative, the researcher believes that the learners will also commit the similar deviations in another compositions such as descriptive, report, recount, etc. Keywords: Error, Error Analysis, Mistake, Mistake Analysis, Linguistic Components, Morphology, Syntax, Lexical.